Perlindungan Merk Bersama dengan Merk Kolektif untuk Menjaga Keaslian Produk Genteng Sokka Kudus - Budi Santoso; Sukresno (Syntax Idea)
One part of Intellectual Property Rights that must be regulated and protected is Brand. The need for legal protection for brands is growing rapidly. One of the brands that needs to be protected is the Sokka Kudus roof tile brand. Brand protection is actually regulated in Law Number 15 of 2001 concerning Trademarks, but in reality many Sokka roof tile brands have not been registered with the General Department of Intellectual Property so they are not protected by law. In this research, using an empirical legal approach and analytical descriptive research specifications, the author tries to explain the use of collective brands as an alternative to collective brand protection which aims to reduce the level of industrial competition. The Regional Government of Kudus Regency plays a role in ensuring that the Sokka brand roof tile industry receives legal protection in accordance with the provisions of Law Number 15 of 2001 concerning Brands. The government, in this case the Ministry of Industry and Trade, supports the use of a collective brand to protect the Sokka tile roof brand.